Analisis Faktor Yang Mempengaruhi Perkembangan Balita di desa Karangraharja Tahun 2023 - ROSI KURNIA SUGIHARTI (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2023)
The growth and development of children physically, mentally, socially, emotionally is influenced by nutrition, health and education. Since the baby is born until the age of one year will experience growth and development. This process takes place rapidly and is highly influenced by the environment however, it lasts very short and cannot be repeated again so it is referred to as the "golden period". Comprehensive and quality development of children's growth and development which is carried out through stimulation activities, early detection and intervention of deviations in the growth and development of toddlers carried out in critical times. The purpose of this study was to determine the factors that influence the development of toddlers. The research design is a non-experimental quantitative survey where data is collected in a cross sectional manner. The data analysis used was Chi Square and Logistic Regression. The results showed that nutritional status, history of LBW, and mother's education affected the development of toddlers with a p value <0.05. The advice given in this study is that mothers are expected to pay more attention to the development of their toddlers so that if there are problems with toddlers they can be resolved..